La gestión documental en la dirección de agua potable y alcantarillado [Dapal] del cantón Latacunga en el período 2022-2023 - Cando Arequipa, Lisbeth Jeaneth (2023)
Document Management is the set of rules and specialized practices that are used to prepare and supervise documents of various kinds, both obtained and prepared, which constitute part of the heritage of public institutions and private companies. For this reason, the purpose of this research is to provide Document Management strategies to improve the management of information in the DAPAL Directorate, due to the fact that there are deficiencies in the management of documentation, which has generated loss and destruction of this document. institutional treasure.